Urgensi MSDM Sebagai Nilai Strategis dalam Mencapai Target Perusahaan - Sejati, Sugeng (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
A synergistic concept between achieving organizational goals and individual goals, so that individual competition or capability can be utilized optimally to achieve both goals. The purpose of this study is to find out how urgent HRM is as a Strategic Value in Achieving Company Targets. This research uses the method of library research (research literature) that is research whose source of information is from various library materials by reading and studying books and writings that have objects with discussion. The results showed that the applied human resource management must contain strategic values that are in accordance with integrated theories and concepts. The application of HR management has a considerable impact on the company's ability to achieve the goals to be achieved. As a company leader, you should think more thoroughly and consider the strategic value of the work program that will be created so that in the future more creative, innovative, and productive so as to minimize the possibility of not achieving organizational targets.